Hypoxia-Inducible Factor 2a Expression Is Positively Correlated With Gleason Score in Prostate Cancer. (22nd March 2021) - Pavlakis, Dimitrios; Kampantais, Spyridon; Gkagkalidis, Konstantinos; Gourvas, Victoras; Memmos, Dimitrios; Tsionga, Aikaterini; Dimitriadis, Georgios; Vakalopoulos, Ioannis
Background: One of the main factors in response to hypoxia in the tumor microenvironment is the hypoxia-inducible factor (HIF) pathway. Although its role in other solid tumors, particularly renal cell carcinoma, has been sufficiently elucidated, it remains elusive in prostate cancer. The aim of the present study was to investigate the expression of main proteins involved in this pathway and determine the correlation of the results with clinicopathological outcomes of patients with prostate cancer. Methods: The immunohistochemical expression of HIF-1a, HIF-2a and their regulators, prolyl hydroxylase domain (PHD)1, PHD2 and PHD3 and factor inhibiting HIF (FIH), was assessed on a tissue microarray. This was constructed from radical prostatectomy specimens, involving both tumor and corresponding adjacent non-tumoral prostate tissues from 50 patients with localized or locally advanced prostate cancer. Results: In comparison with non-tumoral adjacent tissue, HIF-1a exhibited an equal or lower expression in 86% of the specimens (P = 0.017), while HIF-2a was overexpressed in 52% (P = 0.032) of the cases. HIF-1a protein expression was correlated with HIF-2a (P < 0.001), FIH (P = 0.004), PHD1 (P < 0.001), PHD2 (P < 0.001) and PHD3 (P = 0.035). HIF-2a expression was positively correlated with Gleason score (P = 0.017) and International Society of Urological Pathologists (ISUP) grade group (P = 0.022). Conclusions: The findings of the present study suggest a key role for HIF-2a in prostate cancer, as HIF-2a expression was found to be correlated with Gleason score and ISUP grade of the patients. However, further studies are required to validate these results and investigate the potential value of HIF-2a as a therapeutic target in prostate cancer.